Pengaruh Kualitas Produk, Promosi Dan Harga Terhadap Keputusan Pembelian Produk Kosmetik Implora Di Kota Surabaya - Kamelia Masykuroh; Matheous Tamonsang (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2026)
This study aims to examine the influence of product quality, promotion, and price on purchasing decisions for Implora cosmetic products in Surabaya. The sample size was determined using a non-probability sampling method with a purposive sampling technique. The study involved 100 respondents selected based on specific criteria: consumers aged at least 17 years who had purchased and used Implora cosmetic products from cosmetic outlets in Surabaya. This research used a quantitative approach. Data were collected through a questionnaire consisting of several written questions distributed to respondents. The collected data were measured using a Likert scale and analyzed using multiple linear regression. The results show that product quality, promotion, and price have a significant influence on purchasing decisions. These findings indicate that better product quality, more effective promotional activities, and more affordable pricing strategies can increase consumers’ purchasing decisions for Implora cosmetic products in Surabaya. This study provides useful insights for cosmetic businesses in developing more effective marketing strategies.